PERBEDAAN STABILITAS DIMENSI ANTARA CETAKAN ALGINAT YANG DISEMPROT DENGAN LARUTAN NATRIUM HIPOKLORIT 0,5% DAN DETTOL 5% - Wira Putri Winata; Kuswardani Susari Putri; Febrian Febrian (Faculty of Dentistry Universitas Andalas, 2017)
The impression materials that most commonly used in dentistry was alginate. Factors that must be considered was the controlled of infection transmission from alginate, it was important to do disinfection using a disinfectant solution. Alginate had imbibition properties, so that disinfection by spraying technique allowed the expansion of alginate affecting the dimensional stability of impressions. The purpose of this research was to determine the difference between the dimensional stability of alginate impression were sprayed with a solution of sodium hypochlorite 0,5% and Dettol® 5%. The method used was an experimental laboratory with post test only control group design. 27 samples were divided into 3 groups: spraying with 0.5% sodium hypochlorite solution, spraying with 5% Dettol® solution, and spraying with aquades as a controlled. Alginate impressions were sprayed with 0,5% sodium hypochlorite solution, Dettol® 5%, and aquades then filled with gypsum, and then measured dimensional stability by using micrometer screw. Data were analyzed with the Kruskal-Wallis test. The results showed that differences between the dimensional stability of alginate impressions were sprayed with a solution of sodium hypochlorite 0.5% and 5% Dettol® was not significant (p> 0,05). The conclusion of this research was there was no significant difference between the alginate impressions were sprayed with a solution of sodium hypochlorite 0,5% and Dettol® 5% to dimensional stability. Keywords : dimensional stability, alginate, sprayed, sodium hypochlorite, Dettol®